Spatial Modeling for Coal Mines Exploration through Multilevel Data Integration: An Environmental Information System and Applications in CMPDIL, Jharkhand - Dolly Kumari (Recent Progress in Science and Technology Vol. 7, 2023)
The Environmental Information System (ENVIS) is a Gateway on Environment Information that aims to reach a larger segment of society and improve the nation’s ability to manage its environmental resources. Through the inclusion of additional institutions/organizations in the government, academic, corporate, and NGO sectors, as well as others, as an ENVIS center, it has launched a significant initiative to broaden the network and reach. The work aims to use modern information and communication technologies (ICTs) to focus on various subject areas, themes, local conditions, problems, and environmental information. Since January 2002, the Ministry has been working on this project as part of the Environmental Management Capacity Building Technical Assistance Project funded by the World Bank. To facilitate the generation and dissemination of information on environmental issues, the Ministry of Environment & Forest, Government of India, has developed the Environmental Information System (ENVIS). Even though the World Bank project is over, the Indian government has offered financial assistance. The State Government wants to use the facility to accomplish the goals outlined in the project. To ensure that each project is environmentally friendly, CMPDI (Central Mines Planning and Designing Institute) regularly deals with the multi-dimensional environmental complexities present in the coal and other mineral sectors. In order to conduct land use studies for a specific project as well as for urban and regional planning, CMPDI uses satellite, airborne scanner, aerial photography, and ground surveying. Waste management, industrial/domestic effluent treatment, and environmental auditing and monitoring are also done.